Impedance analysis of 0.5Ba(Zr0.2Ti0.8)O-3-0.5(Ba0.7Ca0.3)TiO3 ceramics consolidated from micro-granules - Kaushal, A.
This work aims to contribute new data on the dielectric relaxation behavior of the lead-free piezoelectric 0.5Ba(Zr0.2Ti0.8)O-3-0.5(Ba0.7Ca0.3) TiO3 (BZT-BCT) material processed in aqueous media. To obtain a BZT-BCT ceramic with high density, an aqueous suspension of BZT-BCT material was successfully transferred to spherical granules via freeze granulation, followed by sintering of a consolidated high green dens compact at 1350 degrees C for 4 h. The dielectric relaxation behavior in the temperature range 300-600 degrees C over the frequency range of 0.1 Hz-1 MHz has been carried out to display the characteristic of dielectric relaxation behavior of the BZT-BCT ceramic. Two distinct temperature dependent peaks at characteristic frequencies were observed, which shift towards the high frequency end with increasing temperature, depicting a thermally activated relaxation phenomena in the BZT-BCT ceramic. The dependences of dielectric parameters by fitting data with Cole-Cole equations (Nyquist plot) on temperature have been discussed in detail. Relaxation time was found to decrease with increasing temperature and to obey the Arrhenius relationship. The values of calculated resistances were found to be of same order for bulk (R-b) and grain boundary (R-gb) contributions, whereas capacitance values calculated for bulk (C-b) were found to be 2 orders more than that of capacitance values calculated for grain boundaries (C-gb). (C) 2014 Elsevier Ltd and Techna Group S.r.l. All rights reserved.